VARIANTS OF AITYSH BY POETS SUYUNBAI AND ARSTANBEK - Yelesbay N. (Vestnik Issyk-Kulʹskogo universiteta)
The article examines studies on the aitysh performances of the Kazakh poet Suyunbai Aron uulu and the Kyrgyz poet-improviser Arstanbek Buylash uulu, as well as the Kazakh and Kyrgyz versions of these aitysh. The article also provides information about their surviving manuscripts, collectors of aitysh, and singers who spread the works of both poets among the people. The differences and similarities between the versions are analyzed in a scholarly context. It is also noted that the Kyrgyz poet-improviser Arstanbek Buylash uulu had an excellent command of the Kazakh language and was widely known among the Kazakh people, while Suyunbai Aron uulu was also fluent in Kyrgyz. The author highlights the fact that in Kazakh versions of aitysh, Arstanbek Buylash uulu was known by the name Katagan.